Manifestation of Lithuania’s Nobility’s loyalty on the Occasion of unveiling of the Memorial to Catherine II on 10th September 1904 in Vilnius - Gaidis, Ryšard (Lietuvos istorijos studijos, 2003)
Last two pages missing